Multilevel Analysis of the Effect of School and Peer Group on Smoking Behavior in Adolescents in Banjarnegara - Annisa Widya Panduwinata; Bhisma Murti; Pawito Pawito (Masters Program in Public Health, Sebelas Maret University, 2018)
Background: Smoking remains a public health problem in the world, especially in Indonesia. Indonesia is the third country with the largest number of smokers, especially among teenagers. School and peers are one of the factors that influence smoking behavior in adolescents. This study aims at analyzing the influence of schools and peers on smoking behavior in adolescents.Subjects and Method: This was an analytic observational study with a cross sectional design. It was conducted in Banjarnegara, Central Java, from October to November 2018. A sample of 200 adolescents was selected by simple random sampling. The dependent variable was smoking behavior. The independent variables were intention, attitude, subjective norm, perceived behavior control, pocket money, media exposure, peer, and family intimacy. The data were collected by questionnaire and analyzed by multilevel regression.Results: Smoking behavior was positively affected by intention (b= 1.49; CI95%= 0.25 to 2.73; p= 0.019), peer group (b= 1.20; 95% CI= 0.12 to 2.28; p= 0.030), and media exposure (b= 1.97; 95% CI= 0.87 to 3.08; p<0.001). Smoking behavior was negatively affected by family intimacy (b= -1.34; 95% CI= -2.44 to -0.24; p= 0.017), attitude (b= -1.44; 95% CI= -2.43 to –0. 44; p= 0.005), subjective norm (b= -1.84; 95% CI= -2. 87 to –0.81; p< 0.001), perceived behavior (b=- 1.91; 95% CI= -3.03 to –0.79; p= 0.001). Smoking behavior was negatively affected by money pocket (b= -0.77; 95% CI= -1.85 to 0.30; p= 0.158) but it was statistically non-significant. School had contextual effect of smoking behavior in adolescents (ICC= 13.8%).Conclusion: Smoking behavior is positively affected by intention, peer group, and media exposure. Smoking behavior is negatively affected by family intimacy, attitude, subjective norm, perceived behavior. Smoking behavior is not associated with money pocket. The school has contextual effect of smoking behavior in adolescents.Keywords: smoking behavior, school, adolescents, multilevel analysisCorrespondence: Annisa Widya Panduwinata. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami No. 36 A, Surakarta, Central Java. Email: annisawidya20@gmail.com. Mobile: +6285326744630.Journal of Health Promotion and Behavior (2018), 3(3): 166-178https://doi.org/10.26911/thejhpb.2018.03.03.04